ANALYSIS OF LIVING STAGES OF TRADITIONAL FISHERMEN IN BELANG DISTRICT SOUTHEAST MINAHASA - Laside, Iftitah Khairunnisa; Suhaeni, Siti; Luasunaung, Alfret (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
The purposive of this study, namely to find out how much and what are the sources of income for traditional fishermen's families in Belang District, and the expenses of traditional fishermen's families in Belang District. The Method used in this research is a survey method. The populations in this study are traditional fishermen in Belang District. The sampling method is using a quataed Multi-Stages Purposive Sampling, with the number of sample villages being 15 villages and the sample fishermen taken are fishermen with fishing rods and nets as much as 10% of the total population in each sample village. The data analysis used is descriptive qualitative and quantitative analysis. The standard of living of traditional fishing families is analyzed using the Engel index. Based on the results of the analysis, it is known that the income of traditional fishermen's families in Belang District comes from their main job as fishermen, side jobs outside the field of fisheries. The total incomes of traditional fishermen's families in Belang District on average for one year is Rp.53.394.000. There are two types of expenditures for traditional fishermen's families in Belang District, namely expenditures for food and expenditures for non-food such as clothing, housing, health, education, electricity, transportation and others. The total average expenditure for one year is Rp. 53.394.000, which is divided into expenditures for food needs of Rp. 32.284.500 and expenditures for non-food needs, which are Rp. 21.109.500. The results of the analysis of the Engel index are 60.46%, used to meet food needs only. The proportion for food, which is 39.54%. This is indicates that the standard of living of traditional fishermen in Belang District is still relatively low because more than half of their income is only sufficient to meet food needs.